Assessment of Knowledge, Attitude and Practice Based Survey Towards Successful Restorations of Composite Among practitioners - A, KALYANI BEHERA.; SANDEEP, ADIMULAPU HIMA; S, HARIPRIYA (The journal of contemporary issues in business and government, 2021)
Composite resins are currently the most popular of all tooth coloured restorative materials, which completely replaced silicate cement and acrylic resin as esthetic restorative materials. Aesthetically pleasing restorations are much desirable in current day dentistry and efforts have been made to develop a restorative material to suit the patient's desired needs. The present study by means of a close ended questionnaire evaluates the knowledge, attitude and practice of the endodontists, general dentists, postgraduates and undergraduates towards successful restoration of composite. An online survey form, close ended questionnaires was distributed randomly among 150 respondents. Questions related to 5 knowledge, 5 attitude and 5 practice were presented. All the data was compiled and tabulated in Microsoft Excel and exported to IBM SPSS 20 software and data was represented through chi square tests performed for the comparison between Endodontists, General dental practitioners, Postgraduates and undergraduates. Results were obtained and depicted as graphs which showed the knowledge score as 53.16%, attitude score as 63.82% and practice score as 62.4%. Participants were of mean age groups of 31-40 years of age. More Continuing Dental Education Programmes(CDE),seminars and other educational programmes are required to strengthen the deficit in knowledge and improve treatment planning skills among postgraduate students of Endodontics. Within the limitations of the study, it shows that knowledge with regard to successful composite restoration is moderate, compared to attitude and practice among respondents. It is recommended there is a need for continued professional education and clinical training of the dentists towards all aspects related to composite restorations in order to achieve desired results and esthetics within a stipulated time.